Interest Students of 16 Bandung Public High School in Learning Japanese - Muhammad Ihsan Zulfa Firdaus (WIDAI Japanese Journal, 2020)
Currently, the interest in learning Japanese among teenagers or high school students is increasing, especially in Indonesia. Interest in learning Japanese in adolescents can be influenced by several factors such as themselves, friends, environment, or hobbies, and other factors. All of these factors are grouped into two types of factors, namely internal factors, and external factors. Internal factors can be in the form of aspirations, hobbies, and habits, while external factors can be the environment, parents, friends, and even teachers at school. Based on this, the question arises about what factors influence the interest of adolescents in Indonesia to learn Japanese. And to get the answer, a survey was conducted to Japanese students at 16 Bandung Public High School in August 2019. The survey was carried out by distributing a questionnaire in the form of a google form containing several questions about the supporting factors of interest in learning Japanese to high school students.